45 Effect of Increasing Corn Silage Inclusion in Finishing Diets with or Without Tylosin on Performance and Liver Abscesses - Wilson, Hannah C (J Anim Sci, 2020)
Elevating corn silage inclusion in finishing diets has been investigated and suggests feeding more silage in farming and feeding operations improves profitability, despite decreased gain (ADG) and feed efficiency (G:F). Feeding more silage may decrease liver abscesses and the need for antibiotic control of abscesses. A finishing study was conducted to assess the impact of silage inclusion in finishing diets to reduce the incidence of liver abscesses in beef cattle. A total of 640 (BW = 334 ± 25 kg) steers were utilized in a 2 × 2 factorial treatment design with two levels of corn silage (15 and 45%, diet DM), with or without tylosin for control of abscesses. This study utilized 32 pens of cattle with 20 steers per pen and 8 pens per treatment. There was an interaction for liver abscesses (P = 0.05) and a tendency for an interaction for performance (P = 0.10) between silage and tylosin inclusion but not for carcass traits (P ≥ 0.20). Cattle fed 15% corn silage had the greatest incidence of liver abscesses (34.5%) compared to other treatments (P = 0.05), and abscess rate was decreased to 19% if tylosin was fed. Feeding 45% silage was also effective at lowering liver abscess rates which were 12.4% regardless of whether an antibiotic was fed. Feeding corn silage at 45% of diet DM was as effective as feeding an antibiotic to cattle on 85% concentrate diets. Feeding corn silage at greater inclusions decreased ADG (P ≤ 0.01) but increased final body weight when fed to an equal fatness. However, feeding corn silage at 45% was more economical compared to feeding 15% corn silage, especially at higher corn prices, provided shrink is well managed. Feeding elevated concentrations of corn silage may be an economically viable method to control liver abscesses without antibiotic use.